2019
DOI: 10.1208/s12249-019-1441-9
|View full text |Cite
|
Sign up to set email alerts
|

Liqui-Pellet: the Emerging Next-Generation Oral Dosage Form Which Stems from Liquisolid Concept in Combination with Pelletization Technology

Abstract: In spite of the major advantages that the liquisolid technology offers, particularly in tackling poor bioavailability of poorly water-soluble drugs ( i.e. , BCS Class II drugs), there are a few critical drawbacks. The inability of a high liquid load factor, poor flowability, poor compactibility, and an inability to produce a high dose dosage form of a reasonable size for swallowing are major hurdles, hampering this technology from being commercially feasible. An attempt was therefore mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 47 publications
11
50
1
Order By: Relevance
“…The previous studies by the authors demonstrated that liqui-pellets achieved a high liquid load factor of 1, whilst maintaining excellent flow property [1]. In fact, before the development of liqui-pellet, it has been proven very difficult to achieve such mentioned results, due to the cohesive nature of liquid powder admixture, which is shown in various studies [36][37][38].…”
Section: Evaluation Of Naproxen Liqui-pelletmentioning
confidence: 98%
See 4 more Smart Citations
“…The previous studies by the authors demonstrated that liqui-pellets achieved a high liquid load factor of 1, whilst maintaining excellent flow property [1]. In fact, before the development of liqui-pellet, it has been proven very difficult to achieve such mentioned results, due to the cohesive nature of liquid powder admixture, which is shown in various studies [36][37][38].…”
Section: Evaluation Of Naproxen Liqui-pelletmentioning
confidence: 98%
“…It stems from liquisolid technology; however, liqui-pellet comes under liqui-mass system, which is different from liquisolid system. This liqui-mass system is combined with pelletisation technology, producing liqui-pellet [1]. In recent years, the advancement on the high-throughput screening has indicated an increased number of drug candidates to be either poorly water soluble or insoluble [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations